Oxidative free radicals scavenging activity (in vitro and in vivo assay) of standardized fractions from the seeds of Argyreia speciosa (Ghav-patta) a traditional Indian medicine - Lubna Azmi; Ila Shukla; Arti Goutam; Ch.V. Rao; Talha Jawaid; Amani S. Awaad; Saleh I. Alqasoumi; Osama A. AlKhamees; Mehnaz Kamal (Elsevier, 2019)
Traditional pertinence: Argyreia speciosa Sweet (Linn.), belongs to the family convolvulaceae, a traditional Indian medicinal herb, has been used to treat acute/chronic ulcers, gonorrhea, rheumatoid arthritis and several nervous disorders having a long history. Aim of the study: A broad spectrum approach of this work was to find out the antioxidant activity of Argyreia speciosa seeds, in vitro and in vivo antioxidant assay were performed. Material and methods: Total phenolic content (TPC), reducing power (RP), antioxidant activity (AOA), O2·- (superoxide anion), DPPḢ (1,1-diphenyl-2-picrylhydrazyl) and ̇OH (hydroxyl) radicals scavenging activities, GSH (glutathione), CAT (catalase), SOD (superoxide dismutase) and LPO (lipid peroxidase) are the major parameters which were studied for determining in vitro and in vivo antioxidant property of seed extract & their six fractions obtained from A. speciosa. Carbon tetrachloride (CCl4) induced rat model was used to determine in vivo antioxidant assay of extract and its fractions. Results: Butanol fraction (AS-BF) showed strong antioxidant property and protected oxidative DNA damage. AS-BF was found best as compared to all other fraction for determining antioxidant property of seeds with the reduction in lipid peroxide formation and increment in GSH, CAT and SOD. AS-BF showed the presence of phenolic compounds viz. gallic acid, chlorogenic acid, and ellagic acid. Conclusion: From these results, it was proved that A. speciosa seeds prevent tissue damage due to oxidative stress with strong antioxidant activity. Keywords: Argyreia speciosa, Antioxidant, Polyphenol, Fractionation